Encruamento e evolução microestrutural do alumínio submetido à compressão multiaxial (MAC) após ECAP - Cleber Granato de Faria (2019)
The growing need for materials with multifunctional properties has motivated the development of new alloys and processing techniques. Among these materials, the high strength ones obtained via SPD (Severe Plastic Deformation) stand out. The two most important SPD techniques are ECAP (Equal Channel Angular Pressing) and MAC (Multi-Axial Compression) due to the possibility of processing industrial sized samples, which would allow commercial applications. However, the strength gained by processing is usually accompanied by a ductility loss, which is necessary for further metal forming operations. It has been shown that the mechanical behavior of materials submitted to multi-axial deformation can either work harden or soften. The expected behavior depends on the initial condition and the strain amplitude employed. It was also observed that MAC is capable of increasing work hardening capabilities of previously deformed materials. Therefore, MAC could be used to recover the lost ductility of materials previously submitted to ECAP, further increasing its applications. The present research main goal was to evaluate the influence of low strain amplitude (0.075) MAC on the mechanical behavior of commercial pure aluminum samples (99.97%) previously processed by one ECAP step. The results pointed out that the material softened and partially recovered its work hardening capability after MAC processing. This behavior was attributed to the stabilization of the dislocation structure developed during ECAP to a predominately HAGB (High Angle Grain Boundaries) configuration.